Chapter 7. Plant parasitic nematodes of wheat - Yavuzaslanoglu, Elif; Hekimhan, Hakan; Nicol, Julie; Dababat, Abdelfattah Amer (Springer, 2024)
Plant parasitic nematodes directly or indirectly damage host plants, invading the roots of wheat and other grains. Nematodes not only use a plant’s water and nutrients from the soil or plant but also increase the ability of complex plant pathogenic fungi that cause root diseases to enter the plant. In this case, the damage to the plant is higher than the individual damage. The most common and important plant parasitic nematodes on wheat are Heterodera spp. (cereal cyst nematodes) and Pratylenchus spp. (root lesion nematodes). Many other genera and species cause more local yield and quality losses. Sources of genetic resistance to some nematodes have been identified, but transferring effective genes to commercial varieties takes a long time. Although disease management strategies other than genetic resistance are effective for some nematode species, these strategies are generally neither environmentally nor economically acceptable. Important management strategies, including genetic resistance, combinations of applying chemicals or biological agents to seed or soil, planting non-host crops, or prolonging fallow periods in the problem areas, are still being used in different parts of the world.